Influence of BI Rate, FED Rate, and Inflation on Composite Stock Price Index (JCI) - Mohammad Yusuf; Reza Nurul Ichsan; Sudirman Suparmin (Management Department Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to explain the impact of BI Rate, FED Rate, and Inflation simultaneously, partially, and potentially dominant variable influence on the Composite Stock Price Index by conducting a multiple linear regression analysis. The data is collected monthly from January 2013 to December 2020 with 96-time series data for each free and bound variable. The analysis shows that BI Rate, FED Rate, and Inflation simultaneously significantly affect the Composite Stock Price Index. As the analysis results describe, BI Rate partially negatively influences the Composite Stock Price Index; second, the FED Rate does not affect the Composite Stock Price Index; third, inflation represents a negative influence on the Composite Stock Price Index. In the end, variables that affect the dominant potential of the Composite Stock Price Index are the Rupiah Exchange Rate variables. The results in this study explain the diversity of news on changes in the FED Rate so that investors are confident in their self-assessment to provide results in investing in stocks.Keywords: BI rate, composite stock price index, FED rate, inflation